LHERMITTE-DUCLOS DISEASE: A RARE CEREBELLAR HAMARTOMA PRESENTING FOLLOWING TRAUMATIC BRAIN INJURY AND A REVIEW OF THE LITERATURE - Ashraf, Mohammad; Ahmad Kamboh, Usman; Asif Raza, Muhammad; Choudhary, Nabeel; Mehboob, Mehreen; Shahzad Hussain, Syed; Ashraf, Naveed (Journal of Ayub Medical College Abbottabad, 2022)
Lhermitte-Duclos Disease (LDD) is an extremely rare hamartoma of the cerebellum and is associated with the cancer syndrome Cowden’s disease. We report such a patient whose disease was diagnosed incidental to traumatic brain injury. A 40-year-old male presented after fall from stairs. CT scan revealed a large lesion in the right cerebellar hemisphere. Clinical history recounted multiple short episodes of vomiting (>10 a week) for the past 30 years and development of posterior fossa symptoms over the recent months. Neither of these had him referred due to lack of access to primary healthcare. T1 MRI with contrast showed an isointense focal mass, enhancement along the folia, and distortion of the 4th ventricle. On T2 MRI, tiger striped appearance was noted. Endoscopic third ventriculostomy was performed followed by gross total resection of the hamartoma. Histology confirmed LDD. All reported symptoms resolved following surgery. Due to lack of access to the expensive genetic testing for Cowden’s he is in regular biannual follow up to be evaluated clinically for associated malignancies. We present this case to highlight the clinical-pathological characteristics of LDD, its treatment, and discuss management in the absence of genetic testing in our socio-economic demographic.